Antioxidant Activity of Phenolic Compounds in Ethanolic Extract of Hibiscus sabdariffa L. on Oxidative Stability of Soybean Oil - Hiromoto, Patricia Joho [UNESP]; Umeda, Wellington Mamoro [UNESP]; Jorge, Neuza [UNESP] (Bentham Science Publishers, 2021)
Background: The current interest in natural antioxidants from vegetable sources, mainly in bioactive antioxidants, has been increasing in Brazil. The Hibiscus sabdariffa L. is rich in bioac-tive compounds, besides having antioxidant and antimicrobial properties. Objective: This study aimed to evaluate the antioxidant effect of hibiscus extract on the oxidative stability of soybean oil in an accelerated storage test. Methods: The ethanolic extracts of calyces and hibiscus seeds were evaluated for total phenolic compounds and antioxidant activity using DPPH, FRAP, and β-carotene/linoleic acid. The treatments identified as OS, Tocopherol, Extract, and Mixture, were prepared and submitted to accelerated storage at 60°C. The samples were analyzed on days 0, 6, and 12 for peroxides index, p-anisi-dine, total oxidation value, oxidative stability, and tocopherols. Results: The extract of calyces of hibiscus presented higher amounts of total phenolic compounds and antioxidant activity. Therefore, it was added to soybean oil. The Extract treatment promoted greater efficiency to inhibit the formation of primary and secondary compounds of lipid oxidation. It provided high oxidative stability to the soybean oil, in addition to greater retention of toco-pherols, mainly α-and γ-tocopherol isomers. Conclusion: Among the treatments studied, Extract promoted greater efficiency in the inhibition of the formation of primary and secondary compounds of lipid oxidation, besides providing greater oxidative stability and greater retention of tocopherols during storage.
Keywords: Antioxidants; DPPH; FRAP; Oxidative stability; Phenolic compounds; α-tocopherol